Evaluation of nutrition knowledge and dietary recommendations by coaches of adolescent brazilian athletes - Juzwiak, C. R.; Ancona-Lopez, F. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
The objectives of this study were to describe the dietary practices recommended by coaches working with adolescent athletes and to assess their nutritional knowledge. During a regional competition in the state of Sao Paulo, Brazil, 55 coaches were interviewed. These coaches represented 22 cities with athletes enrolled in Olympic gymnastics, tennis, swimming, and judo events. A 3-section questionnaire was used to obtain data on demographic characteristics, dietary recommendations, and nutrition knowledge. Results showed that all coaches recommended general dietary practices during training, with no specific strategies for pre-, during-, and post-training periods. The main objectives of the recommendations for the training period were weight control and muscle mass gain. Deleterious weight control practices were recommended by 27% of the coaches. Specific dietary practices pre and post competition were recommended by 93% and 46% of the coaches, respectively. Participants responded correctly to 70% (SD = 3.2) of the nutrition knowledge questions, with no significant differences (p = .61) between sports. The knowledge test identified a tendency to overvalue proteins, excessively low-fat diets, and food myths. These findings indicate the importance of developing strategies that will enhance the nutritional training of coaches.